Prerequisites for the transition to a knowledge-based economy in the context of structural transformation, quality of life and economic growth - Makhosheva Salima; Shardan Saida; Gergova Zalina; Uyanaeva Khalimat; Makhoshev Artur (E3S Web of Conferences, 2023)
The modern world is undergoing a rapid structural transformation driven by the growth of intelligent systems and environments. These AI and IoT-based systems provide new opportunities to increase productivity, optimize resources and improve the quality of life. However, the transition to an economy of intelligent systems and environments also introduces challenges and requires a strategic approach. Artificial intelligence is becoming a key driver of the intelligent systems economy. This section of the article analyzes the impact of AI on factory automation, data management and decision making. It also discusses the need to develop an appropriate regulatory and legal framework for the use of AI. The Internet of Things (IoT) allows objects and devices to be connected and exchange data. The article examines the impact of IoT on industry, healthcare, transport and urban infrastructure. The role of standardization and security in the development of IoT is discussed. The transition to an economy of intelligent systems is often accompanied by the automation of routine work tasks. The article examines the impact of automation on the labor market and proposes measures to prepare the workforce for changes in the economy. The rise of the smart system economy provides an opportunity to improve the quality of life of citizens. However, it is necessary to take into account the issues of privacy, security and accessibility of technologies for all segments of the population. This section of the article analyzes the relationship between economic growth and living standards.On the basis of the author’s model of increasing the efficiency of the regional economy, a mechanism for increasing economic growth in the economies of the North Caucasus republics and the Stavropol Territory has been identified. The prevailing role of such factors as: the number of employees, gross regional product, investment, per capita income, etc., factors in ensuring economic growth in the Republic of Dagestan, the Stavropol Territory is proved. At the same time, these factors did not have a decisive influence on the dynamics of the socio-economic development of the Kabardino-Balkarian Republic. Elasticity between factors is calculated, which shows the different architecture of regional economies. Based on them, resource replacement matrices are constructed, the manipulation of which allows you to control the development path of the regional system.